PENERAPAN NILAI KODE ETIK KEDOKTERAN INDONESIA (KODEKI) PADA ERA JAMINAN KESEHATAN NASIONAL DI KABUPATEN INDRAGIRI HILIR - Olvhantiara Sukma; Dedi Afandi; Mohammad Tegar Indrayana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTDoctor as the main doctor that provides health care system in Indonesia ought to have morals and ethics governed by KODEKI. This research aimed to determine the implementation of KODEKI in National Health Insurance in Indragiri Hilir Regency which was examined through 6 values of KODEKI. Thie research used exploration method with qualitative approach towards three doctors with two of them from community health center and one of the from Indragiri Hilir government hospital which were selected using snowball sampling. Data collection was done by interview which is recorded by audio recorder. Results of the research showed that all of the informants possess altruism, responsibility, professional idealism, accountability, scientific integration and social integration values. The results were based on statements as well as attitude given by informants.Key words: KODEKI values, NHC, Indragiri Hilir regency